2006
DOI: 10.1111/j.1651-2227.2006.tb02317.x
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking during pregnancy and hyperactive‐distractible preschooler's: A follow‐up study

Abstract: Aim: To study the association between intrauterine exposure to tobacco smoke and behavioural disorders in preschool children, primarily symptoms of inattention, hyperactivity and impulsivity but also hostile‐aggressive and anxious‐fearful symptoms. Methods: We conducted a follow‐up study in 1355 singletons born to Danish‐speaking mothers. Information on smoking habits during pregnancy and other lifestyle factors was obtained from self‐administered questionnaires filled in during second and third trimester. App… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Second, several studies have found that any level of maternal smoking has effect on offspring health (22), and others have found that some complications related to maternal smoking appear to follow a dose-related pattern (23). In particular, some studies found that maternal smoking of at least 10 cigarettes per day during pregnancy was most likely to be associated with children's externalizing behaviours (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…Second, several studies have found that any level of maternal smoking has effect on offspring health (22), and others have found that some complications related to maternal smoking appear to follow a dose-related pattern (23). In particular, some studies found that maternal smoking of at least 10 cigarettes per day during pregnancy was most likely to be associated with children's externalizing behaviours (24,25).…”
Section: Introductionmentioning
confidence: 99%